Local Perception of The Effects of Climate Uncertainty on Cattle Farming in Burkina Faso: A Case Study of The Mouhoun Province - ZAN, Amadou; Sampebgo, Abdoul-Aziz; Bonkoungou, Joachim; Bassole, Clément Dieudonné (International Journal of Scientific Research and Management (IJSRM), 2024)
Climate change represents a threat to pastoralists in the Mouhoun Province, whose main source of income is the exploitation of natural and animal resources. The problem of this study is based on the good perception of breeders which was necessary for them to adapt to the climatic crises that have already occurred. The objective of this study is to analyze the perception of the effects of climate uncertainty on ruminant breeding in the Mouhoun province. For this purpose, 286 breeders, including agro-breeders and agro-breeders, or 22 breeders per village, were surveyed. In addition, a focus group was organized in each village, for a total of thirteen (13). Phinks software was used to process the individual survey data. The results indicate a deterioration in the forage supply of natural rangelands (100%), an increase in the mobility of animals (69.31%), an increase in morbidity (69.3%) and a drop in the frequency of twin births (56.0%). In summary, it appears that the population has a good perception of the effects of the local climate on animals and forage resources. Furthermore, although it is difficult to integrate research evidence into development policies and practices, the results of this research could guide policy decision-making. This study leads to the conclusion that the changes perceived by breeders are relevant for the development of adaptation strategies to climate change.